The role of transformational leadership in improving the performance of the Hajj and Umrah system - Al-Ghalbi, Mohammad Saad (Journal of Economic, Administrative and Legal Sciences, 2024)
Transformational leadership has become a new perspective that improves performance in various organizations. This study aimed to identify the reality of transformational leadership, and its role in improving the Hajj and Umrah system. Ensure that transformational leadership improves the organizational performance of the system. To achieve the objectives of the research, the researcher used the descriptive approach, and used the questionnaire as a tool for data collection. The study reached a set of results, the most important of which are: - The reality of transformational leadership on workers in the Hajj and Umrah system came to a medium degree and a relative weight (62%). - The reality of performance in the Hajj and Umrah system came to a medium degree with a relative weight (60%). Accordingly, the researcher recommended a number of recommendations, the most important of which are the following: - That the leader of the Hajj and Umrah system adopt a positive trend towards the institution’s vision and mission. To be able to persuade employees to change. - To stimulate creativity and innovation among workers in the Hajj and Umrah system. - To participate with individuals in preparing a future research map for the Hajj and Umrah system. - To encourage employees to present creative ideas and opinions to solve problems. - Shows interest in employees’ opinions and suggestions.